Genetics of the DST-mediated mRNA decay pathway using a transgene-based selection. (1st August 2004) - Lidder, P.; Johnson, M.A.; Sullivan, M.L.; Thompson, D.M.; Pérez-Amador, M.A.; Howard, C.J; Green, P.J.
Abstract : mRNA sequences that control abundance, localization and translation initiation have been identified, yet the factors that recognize these sequences are largely unknown. In this report, a transgene-based strategy designed to isolate mutants of Arabidopsis thaliana that fail to recognize these sequences is described. In this strategy, a selectable gene and a screenable marker gene are put under the control of the sequence element being analysed and mutants are selected with altered abundance of the corresponding marker RNAs. The selection of mutants deficient in recognition of the DST (downstream) mRNA degradation signal is used as a test-case to illustrate some of the technical aspects that have facilitated success. Using this strategy, we report the isolation of a new mutant, dst3, deficient in the DST-mediated mRNA decay pathway. The targeted genetic strategy described circumvents certain technical limitations of biochemical approaches. Hence, it provides a means to investigate a variety of other mechanisms responsible for post-transcriptional regulation.